Frequent medical absences in secondary school students: survey and case–control study. Issue 10 (21st June 2009) - Jones, R; Hoare, P; Elton, R; Dunhill, Z; Sharpe, M
Abstract : Objective: To determine the prevalence of frequent absence (>20% of the school year) for reasons recorded as "medical" in secondary schools; to test the hypothesis that it is associated with physical symptoms and psychiatric disorder and not with serious organic disease; to assess unmet need for psychiatric management. Design: Survey using routinely collected data and case–control study Setting: Local authority secondary schools in Edinburgh, UK. Participants: School students in the first 4 years of secondary school: cases were those with frequent medical absence and controls those with a good attendance record (best 10% of year group), matched for age, gender and school class. Measures: Period prevalence of frequent absences. Cases and controls (students and their parents) completed questionnaires about the students' symptoms. Students were given a psychiatric diagnostic interview and a medical examination. The records of specialist medical services used by the students were reviewed. Results: A substantial minority (2.2%) of students had frequent medical absences. Only seven of 92 (8%) cases had a serious organic disease and 10 of 92 (11%) had symptom-defined syndromes; the remainder had physical symptoms and minor medical illness. Frequent medical absence was strongly associated with psychiatric disorder (45% in cases vs 17% in controls, p<0.001, 95% CI for odds ratio 1.37 to 4.02). Only 14 of the 41 cases (34%) with a psychiatric diagnosis had attended NHS psychiatric services. Conclusions: Frequent absence for medical reasons is common, and more comprehensive management, including psychiatric assessment, is required to prevent long-term adverse consequences.